The Effect of Heat Treatment on the Magnetic and Mechanical properties offe - Ni alloys. - Baghdad Science Journal (مجلة بغداد للعلوم)
The aim of this work is studying the binary system ??'??? Ni?)with two ratios (y=36,80) by using casting method for preparing the samples.Magnetic and Mechanical properties have been studidt different httrea^nttem^rature.All the alloys were found a ferromagnetic behavior and sensitive to the heat treatment. Best properties were found at the heat treatment 1100 C°.A significant different results were found above 1100C° for lower magnetic and mechanical values. This is possibly due to the change on the degree of magnetic moment orders, in which most of the moments are started to remove from coupled ferromagnetically.?